NELAYAN BUBU TARIK DI KEPENGHULUAN SINABOI KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Saharudin "; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This paper examines specifically in the life of fishermen Bubu Tarik and wants to know the adaptation strategies that fishermen use for survival during difficulties, while the location of this study is in Kepenghuluan Sinaboi, District of Sinaboi, Rokan Hilir Regency. Descriptive qualitative methods the method used in this study is using. Where in this study the authors found there were several strategies that the fishermen used to fulfill their needs, namely there were three strategies which were first Active, Passive, and Jetworked. The active strategy carried out by fishermen is Sinaboi's Pull Kepenghuluan, which is doing side work by making salted fish at home, working as a handyman and adding hours of work, also working other according to their abilities. Passive strategy is a survival strategy that is carried out by applying to frugality in spending on family needs, small incomes require fishermen families to withdraw to implement economical living such as reducing the cost of spending children for school, and reducing spending on daily necessities with a minimum. The network strategy carried out by fishermen to attract Sinaboi in the face of financial difficulties, in general, fishermen who attract borrowing money to tauke and fishermen to withdraw only depends on the place where fishermen sell their catch, and complain when there are difficulties, for example when the climate season does not improve.Keywords : The Bubu Tarik fishermen, Strategic of Adaptation, Sinaboi Village